2021
DOI: 10.1101/2021.11.30.470662
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of spatiotemporally changing environment on serial dependence in ensemble representations

Abstract: SummaryThe recent visual past has a strong impact on our current perception. Recent studies of serial dependence in perception show that low-level adaptation repels our current perception away from previous stimuli1–5 whereas post-perceptual decision attracts perceptual report toward the immediate past6–12. In their studies, these repulsive and attractive biases were observed with different task demands perturbing ongoing sequential process. Therefore, it is unclear whether the opposite biases arise naturally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…23,[33][34][35] Indeed, choice history biases scale with uncertainty 19,21,36,37 and adapt to environmental statistics. 21,38 Pascucci and colleagues suggested that the past influences current perception in two ways. 39 Short-term adaptation repels current perception away from past experience, while previous experience attracts perception towards the recent past.…”
mentioning
confidence: 99%
“…23,[33][34][35] Indeed, choice history biases scale with uncertainty 19,21,36,37 and adapt to environmental statistics. 21,38 Pascucci and colleagues suggested that the past influences current perception in two ways. 39 Short-term adaptation repels current perception away from past experience, while previous experience attracts perception towards the recent past.…”
mentioning
confidence: 99%
“…Many studies in the past two decades investigated the efficient nature of perceptual averaging from a set of items (see Introduction). While the main focus in this literature is rapid feature integration from the current trial to form a summary representation, only a few tested the influence of history and found contraction biases in mean estimation tasks for facial expressions ( Crawford et al, 2019 ), orientation ( Manassi et al, 2017 ; Son et al, 2021 ; Tanrikulu et al, 2021 ), and brightness ( Crawford et al, 2019 ). In these experiments, ensembles are presented all at once for a short time, but in real-world environments, groups of items are often dynamically perceived over longer time scales.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is known in literature as the central tendency bias (i.e., the contraction of perceptual judgments toward the mean, or the midpoint of the overall stimulus distribution), as was first described more than a century ago by Hollingworth (1910) . Although serial dependence and central tendency have generally been discussed separately (e.g., Crawford, Corbin, & Landy, 2019 ; Manassi et al, 2017 ; Son et al, 2021 ), they are statistically correlated in many cases as they contract perception toward the same direction (see Tong & Dubé, 2022 ). Whether these biases by priors relating to different time windows originate from different underlying mechanisms, as suggested by the observation that their relative contributions to perception differ in specific populations ( Lieder et al, 2019 ) or from a single mechanism ( Boboeva et al, 2022 ; Tong & Dubé, 2022 ), one needs to study whether they have different characteristics, weights, and impacts on behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations